Rhizobium japonicum Serogroup and Hydrogenase Phenotype Distribution in 12 States - Keyser, Harold H. (1984)
A survey was conducted in 1980 on 972 isolates of Rhizobium japonicum obtained from 65 soybean field locations in 12 states. Isolates were examined for the hydrogenase (Hup) phenotype and somatic serogroup identity. Only 20% of the isolates were Hup(+), with a majority of Hup(−) isolates occurring in 10 of the 12 states. The most predominant serogroup was 31 (21.5%), followed by 123 (13.6%). Although most serogroups contained a majority of Hup(−) isolates, marked differences occurred. None of the isolates in serogroup 135 were Hup(+), but 93% of the isolates in serogroup 122 were Hup(+). The serogroups with relatively high frequencies of Hup(+) isolates (122 and 110) constitute only a small part (<5% each) of the R. japonicum field population in the 12 states.